The Impact of the Socio-Demographic Characteristics of Complementary and Alternative Medicine Users in Serbia on OTC Drug Consumption - Luketina-Sunjka, Marina; Rancic, Nemanja; Mihailovic, Natasa; Jakovljevic, Mihajlo (Frontiers in Public Health, 2019)
The research aims to examine the impact of socio-demographic factors driving Complementary and Alternative Medicine (CAM) users to consume OTC drugs, as to give contribution to better Patient-Centered care provision. Respondents and methods: The study sources data from the latest, third edition of National Health Survey of Republic of Serbia over inhabitants dated in 2013. Sample observed 550 interviewed individuals which practiced CAM over the past year. Depending variable represented the expenditure on OTC drugs over the period of the two last weeks, and independent variables were socio-demographic characteristics. Results: Two thirds (65.3%) of CAM users consume OTC drugs by its full discretion, without physicians’ recommendation or relevant prescription. The users of OTC drugs are more often females, of an average 49.16±16.02 age, possessing secondary school diploma, married and employed, usually living in urban areas, mostly Belgrade, belonging to middle class income group and following the relevant headlines via public information channels (TV, Internet, radio, print). Comparison of results revealed that 2/3 of the respondents that have consumed, and 1/3 of those that did not consume OTC drugs have undergone Fecal occult blood tests over the past year (p<0.05), as well as the fact that those respondents have been less hospitalized in the past year (p=0.05) and that those have more frequently accessed health care services (p<0.05). Conclusion: It is evidential that respondents being CAM and OTC drug users were less times hospitalized, did not use medical leave, and as such another survey could explore this phenomenon into more depth.